Evaluation of mixing profiles for a new micromixer design strategy. Issue 4 (6th November 2015) - Asano, Shusaku; Maki, Taisuke; Mae, Kazuhiro
Abstract : The relationship between mixing history and reaction performance in microreactors using computational fluid dynamics (CFD) simulations is identified. In the idealized, simplified mixing model, mixing proceeds linearly and only the mixing time determined the reaction performance. However, in the case of realistic models where mixing proceeds unequally, the partial rapid progression of mixing, more than the mixing time, significantly impacts the reaction. The use of the fluid segment size distribution to capture this effect is proposed. The effective Damköhler number derived from the fluid segment size distribution predicted the reaction yield well. To demonstrate the utility of the mixing profile design strategy, we fabricated a novel micromixer with multiple partial rapid mixing zones. This micromixer achieved excellent results both in a CFD simulation and an experiment. © 2015 American Institute of Chemical Engineers AIChE J, 62: 1154–1161, 2016